2016
DOI: 10.1080/15257770.2016.1180393
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in exon 6 of the human NT5E gene is associated with aortic valve calcification

Abstract: NT5E encodes ecto-5'-nucleotidase (e5NT, CD73) which hydrolyses extracellular AMP to adenosine. Adenosine has been shown to play a protective role against aortic valve calcification (AVC). We identified two nonsynonymous missense single nucleotide polymorphisms (c.1126A > G, p.T376A and c.1136T > C, p.M379T) in exon 6 of the human NT5E gene. Since both substitutions might affect e5NT activity and consequently alter extracellular adenosine levels, we evaluated the association between NT5E alleles and calcific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Reduced CD73 expression may be associated with the presence of inflammation and contribute to the development of aortic valve dysfunction 16 . This is also consistent with publications where mutations in the NT5E gene, which encodes CD73, lead to altered extracellular nucleotide metabolism and progression in ectopic tissue calcification in the CAVD patient cohort 20,21 . In contrast to these results, it has been reported that stenotic aortic valves can exhibit overexpression of CD73 29 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Reduced CD73 expression may be associated with the presence of inflammation and contribute to the development of aortic valve dysfunction 16 . This is also consistent with publications where mutations in the NT5E gene, which encodes CD73, lead to altered extracellular nucleotide metabolism and progression in ectopic tissue calcification in the CAVD patient cohort 20,21 . In contrast to these results, it has been reported that stenotic aortic valves can exhibit overexpression of CD73 29 …”
Section: Discussionsupporting
confidence: 84%
“…Other deletion effects in mice include dyslipidaemia and intracellular lipid accumulation in muscle, 17 impairment of tubuloglomerular feedback regulation of GFR, 18 and altered thromboregulation and augmented vascular inflammatory responses 19 . Moreover, mutations in the NT5E gene, which encodes CD73, lead to disturbances of extracellular nucleotide metabolism and progression in ectopic tissue calcification in humans 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…As far as rs699664 in GGCX, rs4236 in MGP, and rs2229523 in NT5E genes, data in the literature (30)(31)(32) indicate that SNPs observed in our patients determine either an enzyme activity similar to wildtype (GGCX Arg325Gln and NT5E Thr376Ala ) or absent association with increased risk of calcification (MGP Thr102Ala ) and therefore their functional contribution to the ectopic mineralization phenotype can be likely irrelevant.…”
Section: Resultsmentioning
confidence: 78%
“…The ATP-ADP-AMP-adenosine axis (Figure 1) 1 is an important energy metabolism pathway identified in vivo. The enzymes involved in the axis, including NT5E/CD73 (5ʹ-nucleotidase, ecto), ENPP1 (Ectonucleotide pyrophosphatase/phosphodiesterase 1), and ENTPD1/CD39 (Ectonucleoside triphosphate diphosphohydrolase 1) appear to have an association with severe ectopic calcification, [2][3][4] which was a common complication on hemodialysis (HD) patients and also tightly connected with cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%